Turismo en espacios rurales: su aplicación en la empresa pecuaria "Bacuranao" - Paulet, I.; Valdivia, I.; De León, J.; Estévez, R. (Geographicalia, 2016)
The Empresa Pecuaria Bacurailao is localized in the eastern side of the city of Habana in the municipiums of Guanabacoa and Habana del Este. Its milk production has been destined to the city.A group of specialists of our Faculty studied the problems that the enterprise had in relation to the not rentability of the production of Basic Cooperative Unities (U.B.P.C.) in which it is divided.This group tried to look for solutions to this problem without deviation of its principal activity. It was decided then, to study the possibility of applying tourism in rural space as a solution for the existing problem in the enterprise.It was determined the places in which to carry out the touristic activity in the U.B.P.C. A cartographic method was applied that permitted the evaluation of points that could be used as a lookout station to observe rural scenes with some aesthetic value and to establish the use of the areas around so they remain with the fundamental activity that is carried out.
Keywords: Basic Cooperative Unities (U.B.P.C.); tourism in rural space; lookout station to observe rural scenes.